Broken Buddhas and Burning Temples: A Re-examination of Anti-Buddhist Violence and Harassment in South Korea - Yoon, Young-Hae; Jones, Sherwin (Buddhist Studies Review, 2018)
From 1982 through 2016, Korean media outlets have reported over 120 instances of vandalism, arson and harassment targeting Buddhist temples and facilities in South Korea. An extension of on-going tensions between South Korea’s Buddhist and Evangelical Protestant communities, this one-sided wave of violence and harassment has caused the destruction of numerous temple buildings and priceless historical artifacts, millions of USD in damages, and one death. This article surveys these incidents of anti-Buddhist vandalism, arson, and harassment, analyzing their general characteristics and summarizing major instances of each, before examining the frequency of these incidents within the wider chronology of recent Evangelical-Buddhist tensions. It then examines the responses from South Korea’s Buddhist and Evangelical communities and various government agencies, as well as the effects of these responses, before investigating the relationship between these incidents and the mainstream Evangelical doctrines of religious exclusivism, dominionism and spiritual warfare. The article closes with a discussion of the need for further research into these incidents and the wider Evangelical-Buddhist tensions surveyed herein as well as the relevance of such research to inter-religious conflicts outside Korea.